2011
DOI: 10.1007/s11033-011-0829-8
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary breast cancer in Middle Eastern and North African (MENA) populations: identification of novel, recurrent and founder BRCA1 mutations in the Tunisian population

Abstract: Germ-line mutations in BRCA1 breast cancer susceptibility gene account for a large proportion of hereditary breast cancer families and show considerable ethnic and geographical variations. The contribution of BRCA1 mutations to hereditary breast cancer has not yet been thoroughly investigated in Middle Eastern and North African populations. In this study, 16 Tunisian high-risk breast cancer families were screened for germline mutations in the entire BRCA1 coding region and exon–intron boundaries using direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 49 publications
5
77
0
6
Order By: Relevance
“…Initially, we showed that the TNRC9 gene is amplified and overexpressed in breast cancer, particularly in advanced stages. Our previous investigations suggest that Arab women may experience an earlier age of onset and a preponderance of aggressive breast cancer phenotype (32) and highlighted the importance of BRCA1 gene in the etiology of breast cancer in Arab population (33). Our current findings, showing a significant association between TNRC9 gene amplification and reduction in diseasefree and metastasis-free survival rates, suggest that TNRC9 could be involved in the onset of aggressive forms of breast cancer, found more frequently in Arab populations.…”
Section: Discussionsupporting
confidence: 62%
“…Initially, we showed that the TNRC9 gene is amplified and overexpressed in breast cancer, particularly in advanced stages. Our previous investigations suggest that Arab women may experience an earlier age of onset and a preponderance of aggressive breast cancer phenotype (32) and highlighted the importance of BRCA1 gene in the etiology of breast cancer in Arab population (33). Our current findings, showing a significant association between TNRC9 gene amplification and reduction in diseasefree and metastasis-free survival rates, suggest that TNRC9 could be involved in the onset of aggressive forms of breast cancer, found more frequently in Arab populations.…”
Section: Discussionsupporting
confidence: 62%
“…This mutation was also found in four Algerian families (Uhrhammer et al, 2008;Cherbal et al, 2010), three unrelated Tunisian families (Mahfoudh et al, 2011) and recently in a Moroccan patients (Tazzite et al, 2012;Laraqui et al, 2013) . These findings suggest the presence of a founder effect mutation in the Mediterranean population.…”
Section: C798_799delttmentioning
confidence: 55%
“…El riesgo de desarrollar CGM en individuos portadores de alguna mutación en BRCA es del 45% al 80%; para el cáncer de ovario es del 45% al 60% (Mahfoudh et al, 2012;Narod & Rodríguez, 2011;O'Donovan & Livingston, 2010;Paul & Paul, 2014). Algunos estudios de familias con antecedentes de inicio de CGM a edad temprana sugieren que las mutaciones en el gen BRCA1 son responsables de aproximadamente el 50% de los casos de este tipo de cáncer, del 90 % de los casos de CO y hasta de un 95% de riesgo global para ambos tumores (Lynch et al, 2013;Seong et al, 2014).…”
Section: Discussionunclassified